Microsurgical training in vein anastomoses: the use of systemic heparin in a rat model - Passiatore, Marco; Taccardo, Giuseppe; D'Orio, Marco; Stomeo, Daniele; Starnoni, Marta; De Vitis, Rocco (Acta Biomedica Atenei Parmensis, 2023)
Objective. To investigate whether the use of systemic heparin could be useful for vein microvascular anastomoses in microsurgical training on rats.Materials and Methods. Design: Femoral end-to-end venous anastomoses were performed on both thighs of 40 wistar rats by two microsurgery trainees from October 2018 to February 2019 (80 anastomoses in total). We divided the rats into 2 groups of 20 specimens (40 femoral end-to-end anastomoses) each: group A received no heparin administration; group B received subcutaneous systemic heparin administration before starting dissection. We compared both vein patency after the procedures.Results. Patency tests showed no difference between the two groups after 5 minutes. At the delayed test after 120 minutes, vein patency was significantly better in the systemic heparin group (85,0% vs 55,0%). Even though both trainees judged practicing on both groups very instructive, they found useful performing anastomoses when heparin was administrated.Conclusion. We suggest including the use of systemic heparin in microsurgery training programs, especially for the beginners. Systemic heparin administration in rat models is educative for trainees.